PENGARUH BUDAYA ORGANISASI TERHADAP EFEKTIVITAS PENERAPAN AKUNTANSI SEKTOR PUBLIK SERTA DAMPAKNYA TERHADAP GOOD GOVERNANCE (Studi Pada Satuan Kerja Perangkat Daerah di Kota Malang) - Zanuar Priyatno; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This study aims to determine the Effect of Organizational Culture on the Effectivenessof Public Sector Accounting Implementation on Regional Work Unit (SKPD) In Malang. Thisresearch was conducted on the Regional Performance Work Unit (SKPD) Malang City SpecialKelurahan by using the census method. Data collection was done by spreading questionnairesquestionnaire and browsing in Malang City Government Website. Data analysis and hypothesistesting is done by using Path Analysis (Path Analysis).The results showed that: (1) Organizational Culture has significant effect on theEffectiveness of Public Sector Accounting Implementation. This shows that organizationalculture contributes enough in improving the effectiveness of public sector accountingapplication, (2) Effectiveness of Public Sector Accounting Implementation has significant effecton Good Governance. The value of C.R in Regression Weight is 2,266, so that the effectivenessof good and proper accounting application can lead to better governance system.Keywords: Effectiveness, Public Sector Accounting, Good Governance, Organizational Culture.